PENGARUH KERJASAMA TIM DAN PENGEMBANGAN KARIR TERHADAP KINERJA KARYAWAN PADA PT BANK PAPUA CABANG MAKASSAR - Novita Fanesia Brianti Paseno; Megawaty Megawaty (Jurnal Bisnis dan Kewirausahaan, 2023)
This study aims to determine and analyze the effect of teamwork and career development on employee performance at PT. Makassar Branch of Bank Papua. The type of data used is quantitative with primary data sources with 50 employees as respondents. The sampling technique used in this study is saturated sampling. The data analysis used in this study was multiple linear regression analysis using the SPSS version 26 application. The partial results showed that teamwork had a positive and significant effect on employee performance and career development had a positive and significant effect on employee performance. The simultaneous research results show that teamwork and career development have a positive and significant effect on employee performance.